Water Environment in Macro-Tidal Muddy Sanmen Bay - Li Li; Lihong Wu; Jinxiong Yuan; Xinyu Zhao; Yuezhang Xia (Journal of Marine Science and Engineering)
The water environment in estuaries is a crucial factor affecting the biodiversity and self-purification capacity of coastal zones. This study focuses on Sanmen Bay as an example to study the characteristics and temporal variations of the water environment in the turbid coastal waters on the East China Sea coast. The field data of hydrodynamics and water environment from 2018 to 2023 including different seasons in the bay were collected and analyzed. We analyzed the correlation between water environmental factors and sediment and explored the impact of sediment mixing layers on the water environment. Field data indicate that water temperature, dissolved oxygen content, and suspended sediment concentration (SSC) vary seasonally. In summer, the water temperature and SSC are the highest; in autumn, the dissolved oxygen content is the highest. Salinity and pH values showed little variation from 2018 to 2023. The concentration of oils in sediments across the entire area within Sanmen Bay varied from 2018 to 2023, which decreased from (30.6–92.2) × 10−6 mg/L to below 10−6 mg/L. Correlational analysis indicates that dissolved oxygen concentration and heavy metal content were correlated with sediment in 2018, with correlation coefficients of approximately 0.5. Sediments impact the water environment through changing stratification and mixing due to suspended particulate matter and through changing water environment parameters (e.g., heavy metal) due to bed sediment erosion. The bulk Richardson number in most areas is larger than 0.25. These results indicate that sediment impacts heavy metals in Sanmen Bay. In highly turbid waters, sediments are more likely to adsorb heavy metals and other pollutants, thereby impacting water quality.